Uganda : Technical Assistance Report-Report on the Financial Transactions and Balance Sheets Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding development of financial transactions and balance sheets. The IMF mission suggested developing the financial transactions and balance sheets based on a holistic approach following the integrated sectoral accounts framework of the 2008 System of National Accounts. This approach will highlight the interconnection of the four main sectors of the Ugandan economy. The IMF mission judged that development of experimental financial transactions and sector balance sheets is possible in the near future. However, the development of final accounts that are consistent with nonfinancial accounts would take two to three more years and would depend on acquisition of additional source data.